Product Innovation of Deposits in Islamic Banking: Challenges and Opportunities After the Enforcement of the Islamic Financial Services Act 2013 - Nik Abdul Ghani, Nik Abdul Rahim; Mohd Saffai @ Mohd Shafie, Mastura (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This article aims to analyze the changes in the structure and operations of deposit products in Islamic banking following the enforcement of the Islamic Financial Services Act 2013 (IFSA). The stricter Shariah compliance requirements and regulations introduced by IFSA have affected how Islamic banking institutions classify and offer their deposit products. The main issue faced is how Islamic banking institutions can maintain the competitiveness of their deposit products while ensuring adherence to Shariah principles and strict regulatory requirements. The objective of this study is to identify the challenges and opportunities in Islamic deposit product innovation, as well as strategies that can be used to attract customer interest and enhance their understanding of these products. The methodology used in this study involves content analysis and semi-structured interviews with officers from Bank Islam and Bank Muamalat, two leading Islamic banking institutions in Malaysia. The findings show that there is an urgent need for innovation in Islamic deposit products, particularly in the use of Shariah contracts such as wakalah and tawarruq. The study also found that while there are challenges in ensuring Shariah compliance, there are significant opportunities to enhance the competitiveness of Islamic deposit products through more effective marketing strategies and improved customer understanding. This article provides an in-depth insight into the potential and obstacles in the development of Shariah-compliant Islamic deposit products, as well as recommendations for improvements in the operations and offerings of these products.